DEMOCRATIC MANAGEMENT IN EARLY CHILDHOOD EDUCATION: A LITERATURE REVIEW ON AUTISM SPECTRUM DISORDER (REMUNOM, 2025)
This article focuses on a literature review of works that address democratic management and the inclusion of students with Autism Spectrum Disorder (ASD) in Early Childhood Education, between the years 2018 and 2023. The research is a study with a qualitative methodological approach, through a literature review of a total of 15 (fifteen) productions, involving theses, dissertations and articles that are part of the SCIELO (Scientific Electronic Online) electronic library, the Digital Library of the Brazilian Institute of Information in Science and Technology (IBICIT) and the CAPES Theses and Dissertations Catalog. These works aimed to identify the first studies on the topic and the main concepts used; identify the places where the topic is most researched (area of ​​knowledge; in research programs in Brazil and in which regions); explain the associated subthemes; the main theories (epistemologies and theorists used) used; the results and the gaps. The studies show that research on the topic is concentrated in postgraduate programs in the Southeast and South regions, and that the most common subtopics include inclusive pedagogical practices, teacher training, and public policies for special education. The most widely used methodology was qualitative research, with case studies and document analysis. The results indicate a growing interest in teacher training and inclusion policies but highlight gaps in the specific analysis of school management in the context of the inclusion of students with ASD in Early Childhood Education. It is concluded that there is an urgent need to deepen studies on the role of school management in the inclusion of students with ASD, especially in Early Childhood Education, to support more effective pedagogical practices and more inclusive public policies.